Ibrutinib Displays Atrial-Specific Toxicity in Human Stem Cell-Derived Cardiomyocytes - Sanam Shafaattalab; Eric Lin; Effimia Christidi; Haojun Huang; Yulia Nartiss; Analucia Garcia; Jeehon Lee; Stephanie Protze; Gordon Keller; Liam R. Brunham; Glen F. Tibbits; Zachary Laksman (2019)
Ibrutinib (IB) is an oral Bruton's tyrosine kinase (BTK) inhibitor that has demonstrated benefit in B cell cancers, but is associated with a dramatic increase in atrial fibrillation (AF). We employed cell-specific differentiation protocols and optical mapping to investigate the effects of IB and other tyrosine kinase inhibitors (TKIs) on the voltage and calcium transients of atrial and ventricular human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs). IB demonstrated direct cell-specific effects on atrial hPSC-CMs that would be predicted to predispose to AF. Second-generation BTK inhibitors did not have the same effect. Furthermore, IB exposure was associated with differential chamber-specific regulation of a number of regulatory pathways including the receptor tyrosine kinase pathway, which may be implicated in the pathogenesis of AF. Our study is the first to demonstrate cell-type-specific toxicity in hPSC-derived atrial and ventricular cardiomyocytes, which reliably reproduces the clinical cardiotoxicity observed.